Composition and Architecture Design of Double‐Shelled Co0.85Se1−xSx@Carbon/Graphene Hollow Polyhedron with Superior Alkali (Li, Na, K)‐Ion Storage. Issue 17 (6th April 2020) - Wang, Chunhui; Zhang, Bao; Xia, Haifeng; Cao, Liang; Luo, Bi; Fan, Xinming; Zhang, Jiafeng; Ou, Xing
Abstract: The exploration of materials with reversible and stable electrochemical performance is crucial in energy storage, which can (de) intercalate all the alkali‐metal ions (Li +, Na +, and K + ). Although transition‐metal chalcogenides are investigated continually, the design and controllable preparation of hierarchical nanostructure and subtle composite withstable properties are still great challenges. Herein, component‐optimal Co0.85 Se1− x S x nanoparticles are fabricated by in situ sulfidization of metal organic framework, which are wrapped by the S‐doped graphene, constructing a hollow polyhedron framework with double carbon shells (CoSSe@C/G). Benefiting from the synergistic effect of composition regulation and architecture design by S‐substitution, the electrochemical kinetic is enhanced by the boosted electrochemistry‐active sites, and the volume variation is mitigated by the designed structure, resulting in the advanced alkali‐ion storage performance. Thus, it delivers an outstanding reversible capacity of 636.2 mAh g −1 at 2 A g −1 after 1400 cycles for Li‐ion batteries. Remarkably, satisfactory initial charge capacities of 548.1 and 532.9 mAh g −1 at 0.1 A g −1 can be obtained for Na‐ion and K‐ion batteries, respectively. The prominent performance combined with the theory calculation confirms that the synergistic strategy can improve the alkali‐ion transportation and structure stability, providing an instructive guide for designing high‐performance anode materials for universal alkali‐ion storage. Abstract : The component‐optimal Co0.85 Se1− x S x nanoparticles are fabricated by a facile route of in situ sulfidization of metal organic framework, which are intimately wrapped by the S‐doped graphene network, constructing a hollow polyhedron framework with double carbon shells (CoSSe@C/G). Benefiting from the synergistic effect of composition regulation and architecture design by S‐substitution, the target material exhibits an excellent alkali‐ion (Li +, Na +, and K + ) storage performance.